Transgenic Bt maize in South-and Central America: the pros and cons - Zenner-de-Polanía, Ingeborg (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2021)
The official authorization for planting Bt maize in most Central and South American countries was granted more than 20 years ago. This permission has raised concerns, has revealed inconsistencies in the information provided for farmers, has shown unknowns, motivating comments, and produced publications, often not scientific. Given the theoretical impact on environment, economy, and health, and the development of fall army worm´s resistance, despite the existing research capacity in these countries, the scientific literature is scarce, probably due to lack of funding and influence by the holders of the patents and the producers and traders of seeds of transgenic maize. The aim of this review is to debate the benefits and disadvantages originated by the sowing of the maize hybrids that contain any of the different Cry´s of the bacteria Bacillus thuringiensis. The documents reviewed do not elucidate conclusions; it will be necessary to wait years to define if the transgenic maize plantings represented a benefit for the growers and consumers of this plant species, which originated in these areas. However, at this moment an existing balance between the benefits and the risks of Bt maize plantings could be deduced.